Vacinação com células de melanoma B16-F10 expostas à Cromomicina A5 induz ativação da imunidade antitumoral - Fernandes, Keilla Santana da Silva (2024)
Cancer is a set of diseases with complex biology posing the second cause of death in the world. Metastatic melanoma is a type of cancer highly aggressive, and the most effective therapies still show limited responses in less than half of patients. Some first-line cytotoxic chemotherapy drugs, such as doxorubicin and paclitaxel, induce the activation of the patient's immune system by inducing immunogenic cell death (ICD), which is a rare type of regulated cell death. ICD inducers produce more effective and long-lasting responses against cancer. Tumor cells, when subjected to this type of death, function as a vaccine, releasing danger signals, which are damage-associated molecular patterns (DAMPs), as well as tumor antigens, which can be recognized by the immune system. Chromomycins (CAs) are molecules produced by bacteria of the genus Streptomyces that have important biological activities, such as cytotoxicity against tumor cells, and are considered promising for application in the pharmacological area. Therefore, in this study, the activation of antitumor cellular immunity was evaluated through the vaccination of female Mus musculus mice of the Black C57BL/6 lineage with B16-F10 melanoma cells pre-exposed to chromomycin A5 (CA5). Vaccination of the animals was the initial stage of the immunophenotyping experiments of dendritic cells (DCs) and lymphocytes, as well as the cytotoxicity test of splenocytes from animals vaccinated against B16- F10 melanoma cells. These experiments culminated in flow cytometry analysis. In addition to these experiments, cytokine levels were measured by enzyme- linked immunosorbent assay (ELISA) in both serum from vaccinated animals and naïve splenocytes in co-culture with B16-F10 cells exposed to CA5. It was observed that exposure to CA5 induces the release of pro-inflammatory cytokines. Stimulation of splenocytes in vitro with B16-F10 cells exposed to CA5 induces releasing of tumor necrosis factor-α (TNF-α) and analysis of serum from vaccinated animals showed the release of interleukin-12/23 (IL- 12/IL-23). It was also seen that vaccination with B16-F10 cells exposed to CA5 activates DCs and T lymphocytes. The activation of DCs was evidenced, in addition to the production of cytokines, by the increase in the population of type-2 conventional DCs (cDC2) (CD11b+CD11c+) and the expression of the activation markers CD80, CD86 and MHC-II on the surface of these cells. Vaccination also activated the type-1 cDC population (CD11b-CD11c+), which was seen by increased expression of CD80 and CD86. The activation of T lymphocytes was evidenced by the increased expression of the markers CD69, CD25 and CD44high on CD4+ T and CD8+ T lymphocytes. All aforementioned results showed p < 0.05. The present study showed antitumor immune activation in animals vaccinated with B16-F10 cells exposed to CA5. These results encourage additional studies on the preclinical development of CA5 as a possible anticancer drug.